A carbon–oxygen-bridged hexacyclic ladder-type building block for low-bandgap nonfullerene acceptors. (2nd February 2018) - Li, Ting; Zhang, Honghong; Xiao, Zuo; Rech, Jeromy J.; Niu, Helin; You, Wei; Ding, Liming
Abstract : A ladder-type unit (COi 6) and three related acceptors were developed. FTAZ:COi 6FIC solar cells gave a power conversion efficiency of 9.12%. Abstract : A hexacyclic carbon–oxygen-bridged ladder-type unit, COi 6, was developed. Three nonfullerene acceptors (COi 6IC, COi 6FIC and COi 6DFIC) based on COi 6 were prepared. They present low optical bandgaps of 1.31–1.37 eV and strong absorbance in the near-infrared region. A 9.12% power conversion efficiency was achieved from the solar cells based on COi 6FIC and a wide-bandgap copolymer donor (FTAZ).